Russia’s Policy in the Middle East in the Context of the Crisis in Syria: Challenges and Opportunities - Ahmad Naser Vakhshiteh (RUDN Journal of Political Science, 2018)
The article is devoted to the analysis of the foreign policy of the Russian Federation in the Middle East’s region. The author examines the evolution and transformation of this policy in the context of the Syrian crisis. The theoretical basis of the study was the theory of realistic school, the theory of “balance of power”, the concept of “balance of threats” by Stephen Walt and “securitization” of the Copenhagen school. The author comes to the following conclusions: Russian foreign policy in the Middle East after the collapse of the Soviet Union has gone through several stages of development from almost complete suspension in solving regional problems to an active role not only as a player, but also as a mediator of many regional processes, and above all the Syrian crisis. The article also attempts to forecast the situation in the Middle East from the point of view of opportunities and challenges for Russia.